Effect of Adding Ascorbic acid on the Physicochemical and Rheological Properties of Soft Wheat Flour Infested with Sunn Pest (Damascus University Journal of agriculture sciences, 2024)
This research was conducted at the laboratories of Food Sciences Department, Faculty of Agriculture, Damascus University, and the Central Grain Laboratory, Ministry of Internal Trade and Consumer Protection, with the aim of studying the effect of the degree of sunn pest infestation on softwheat grains (as a percentage) on the physicochemical and rheological properties of these grains, and working to improve quality characteristics of affected wheat grain by adding different proportions of ascorbic acid.The results of evaluating the physicochemical indicators of the flour produced from wheat samples infected with different percentages of the sunn pest showed a decrease in these indicators with the increase in the percentage of grains infested with sunn, and the percentage of decrease in the quantitative and qualitative indicators of proteins at the 10% percentage of infection was (18.68%) for the percentage of total proteins, (26.52%) ) for the percentage of wet gluten, (28.87%) for the percentage of dry gluten and (35.30%) for the gluten index. In addition, the infestation of the sunn insect significantly affected all the studied farinograph values, the properties of the flour deteriorated clearly with the increase in the percentage of infested grains in the wheat mass, as the water absorbency of the flour, dough development time and dough stability decreased and the degree of weakness of the dough increased, and thus, the results in this research indicated that infesting wheat grains with the sunn pest would reduce the strength of the flour and change the manufacturing direction of the flour. On the other hand, the addition of ascorbic acid to the flour produced by grinding samples of studied wheat grains infected with different percentages of the sunn insect led to an improvement in the qualitative properties of the proteins. This was also accompanied by an improvement in the rheological properties of the flour, and this study also indicated that the gluten index test could be a very useful method for detecting wheat damaged by the sunn bug.
Keywords: Rheological Properties; Ascorbic Acid; Sunn Insect; High Quality Flour; Physicochemical Properties